Leptospirosis - Chierakul, Wirongrong (Manson's Tropical Infectious Diseases, 2014)
• Leptospirosis is caused by eight pathogenic Leptospira species, which have many mammalian animals as reservoirs. Humans are accidental and dead-end hosts, who contact directly or indirectly with Leptospira-contaminated water or animal products. • Many infections in endemic areas are asymptomatic or oligosymptomatic. • Clinical manifestations are those of a nonspecific acute febrile illness. Complications such as cholestatic jaundice, aseptic meningitis, acute renal injury, haemorrhage especially in the lung and myocarditis can occur and lead to a fatal outcome. Overall mortality is less than 10%. • Clinical diagnosis is important but nonspecific. Laboratory diagnosis is not practical for patient care, but very important for epidemiology, since both culture and serology take a relatively long time. • Differential diagnoses are dengue and other haemorrhagic fevers, malaria, scrub typhus, hepatitis, yellow fever, Hantavirus (both HPS and HFRS), enteric fever and other bacterial sepsis, especially in patients with severe complications. • Antibiotic treatment should be given as early as possible. Doxycycline is the drug of choice in uncomplicated cases; penicillin, doxycycline, ceftriaxone and cefotaxime are efficacious alternatives in severe cases. • No effective human vaccine available, protection from contact is crucial. Weekly doxycycline chemoprophylaxis in very high-risk groups is also effective.